Reduction in Restraint and Critical Incidents in a Norwegian Residential Treatment Facility for Children Aged 7–13 Following the Implementation of the Neurosequential Model of Therapeutics - Ann-Karin Nielsen Bakken; Kaja Næss Johannessen; Erin P. Hambrick; Ole André Solbakken (Youth)
In child and adolescent inpatient, residential and day-treatment facilities, the use of physical restraints and the occurrence of critical incidents are a significant problem. Restraints may sometimes be necessary if a child exhibits dangerous aggressive behavior, but may also be misused or overused, and have been shown to be preventable in many cases. This study aims to investigate if the implementation of the Neurosequential Model of Therapeutics (NMT) has an effect on the annual number of physical restraint incidents in a residential treatment facility for children with complex mental health disorders. Data before and after NMT implementation were collected from the agency’s restraint records. The results showed that post-NMT implementation, there was a substantial and sustained reduction in restraint incidents, with a Cohen’s d value of 2.03, indicating a very large effect. Limiting restraint use in treating children with complex mental health disorders can foster a safer and more therapeutic environment, with potential improvements in treatment outcomes. This study demonstrated a substantial drop in restraint incidents following the implementation of the Neurosequential Model in a residential facility for children aged 7–13. This reduction is presumably pivotal for children with complex mental health disorders, making treatment less coercive and offering promise for settings in which restraint incidents are a concern.